IMPROVEMENT OF LEARNING ACTIVITIES AND ACHIEVEMENT OF STUDENT LEARNING OUTCOMES IN LEARNING PHYSICS USING INQUIRY TRAINING LEARNING MODEL - Rahayu, Puji (Journal of Learning and Technology in Physics, 2021)
Teaching and learning activities not only require students to obtain good cognitive learning outcomes but also require students to be able to play an active role in learning so that students have good attitudes and skills as well. Student activeness can be seen from the activities or activities during learning. Therefore, this study aims to determine the increase in student learning activities and student learning outcomes using the Inquiry Training learning model. This type of research is a quasi experiment. The instrument used was the observation sheet in accordance with the learning model applied and the learning outcome test in the form of an essay totaling 10 items. The results showed that an increase in student learning activities would affect the achievement of student learning outcomes.